Enhancing all-in-one bioreactors by combining interstitial perfusion, electrical stimulation, on-line monitoring and testing within a single chamber for cardiac constructs. Issue 1 (December 2018) - Visone, Roberta; Talò, Giuseppe; Lopa, Silvia; Rasponi, Marco; Moretti, Matteo
Abstract Tissue engineering strategies have been extensively exploited to generate functional cardiac patches. To maintain cardiac functionalityin vitro, bioreactors have been designed to provide perfusion and electrical stimulation, alone or combined. However, due to several design limitations the integration of optical systems to assess cardiac maturation level is still missing within these platforms. Here we present a bioreactor culture chamber that provides 3D cardiac constructs with a bidirectional interstitial perfusion and biomimetic electrical stimulation, allowing direct cellular optical monitoring and contractility test. The chamber design was optimized through finite element models to house an innovative scaffold anchoring system to hold and to release it for the evaluation of tissue maturation and functionality by contractility tests. Neonatal rat cardiac fibroblasts subjected to a combined perfusion and electrical stimulation showed positive cell viability over time. Neonatal rat cardiomyocytes were successfully monitored for the entire culture period to assess their functionality. The combination of perfusion and electrical stimulation enhanced patch maturation, as evidenced by the higher contractility, the enhanced beating properties and the increased level of cardiac protein expression. This new multifunctional bioreactor provides a relevant biomimetic environment allowing for independently culturing, real-time monitoring and testing up to 18 separated patches.